Teaching Eco-Literacy: What is The Challenge in Indonesian Elementary School - Ningrum Perwitasari; Zela Septikasari; Yogi Prihandoko (Jurnal Ilmiah Profesi Pendidikan, 2025)
Environmental awareness is an important part of environmental sustainability, but environmental awareness in society, including students, is still low. This can be seen from various studies conducted previously. Eco-literacy is one of the skills that can increase environmental awareness, but it is still rarely studied. This study aims to evaluate how eco-literacy has been implemented, the challenges in implementing eco-literacy, and the ideal implementation of eco-literacy for teachers in elementary school. Data collection was conducted using qualitative methods and quistionnaire techniques. Sixty teachers from Yogyakarta, Central Java, and Jakarta were interviewed. The results of the research show that eco-literacy has been implemented in elementary schools through subjects, the challenges teachers face in implementing eco-literacy are learning methods, media, and learning resources and teachers hope that eco-literacy can be implemented based on constructivist learning theory with appropriate syntax.  Based on the findings in this study, it can be concluded that eco-literacy has been implemented in elementary schools, but there are still many challenges faced so that eco-literacy can be successfully implemented.